Impact of smoking status on platelet function and clinical outcomes with prasugrel vs. clopidogrel in patients with acute coronary syndromes managed without revascularization: Insights from the TRILOGY ACS trial - Jan H. Cornel (2018)
Background To further explore the impact of smoking on antiplatelet activity and treatment response, we evaluated time-dependent relationships between smoking status with on-treatment platelet reactivity and clinical outcomes for prasugrel vs. clopidogrel in patients with acute coronary syndromes managed medically without revascularization. Methods and Results A total of 7062 patients aged <75 years from the primary TRILOGY ACS cohort randomized to prasugrel vs. clopidogrel were evaluated through 30 months by baseline and time-dependent smoking status with adjusted proportional-hazards models. A total of 1613 participants (23%) were included in a platelet function sub-study evaluating serial P2Y12 reaction unit (PRU) measurements. Current smokers (n = 1566 [22%]) at baseline had fewer comorbidities compared with non-smokers; nearly half quit smoking during follow-up. Although median on-treatment PRU values were lower with prasugrel vs. clopidogrel, persistent smokers had lower serial PRU values in both treatment groups compared with non-smokers, with no differential interaction of treatment response by smoking status. The frequency of cardiovascular death, myocardial infarction, or stroke in current smokers was significantly lower with prasugrel (11.7%) vs. clopidogrel (18.6%), but there was no difference in non-smokers (13.8% vs. 13.7%), with significant interaction between treatment and baseline smoking status (P =.0002). Bleeding events occurred more frequently in prasugrel-treated patients with no significant interaction between treatment and baseline smoking status. Conclusions Among medically managed ACS patients <75 years of age, the risk of ischemic outcomes was significantly reduced with prasugrel vs. clopidogrel among smokers vs. non-smokers. No interaction between on-treatment platelet reactivity and smoking status was found. © 2014 Mosby, Inc.